2016
DOI: 10.1038/srep27104
|View full text |Cite
|
Sign up to set email alerts
|

TLR9-ERK-mTOR signaling is critical for autophagic cell death induced by CpG oligodeoxynucleotide 107 combined with irradiation in glioma cells

Abstract: Synthetic oligodeoxynucleotides containing unmethylated CpG dinucleotides (CpG ODN) function as potential radiosensitizers for glioma treatment, although the underlying mechanism is unclear. It was observed that CpG ODN107, when combined with irradiation, did not induce apoptosis. Herein, the effect of CpG ODN107 + irradiation on autophagy and the related signaling pathways was investigated. In vitro, CpG ODN107 + irradiation induced autophagosome formation, increased the ratio of LC3 II/LC3 I, beclin 1 and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…MEK/ERK pathway is a common intracellular signaling pathway related to glioma cell proliferation [ 24 ]. Our study also demonstrated the role of MEK/ERK pathway in the proliferation and migration of glioma cells induced by P2X 7 R activation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MEK/ERK pathway is a common intracellular signaling pathway related to glioma cell proliferation [ 24 ]. Our study also demonstrated the role of MEK/ERK pathway in the proliferation and migration of glioma cells induced by P2X 7 R activation.…”
Section: Resultsmentioning
confidence: 99%
“…In tumor cells, members of the MEK/ERK pathway encoding genes are often mutated and become overactivated, which causes this pathway to be important for the development of many human tumors such as breast cancer, thyroid carcinoma, and squamous cell carcinoma [ 46 , 47 ]. The MEK/ERK pathway also plays a critical role in the development of gliomas [ 24 , 48 , 49 ]. The MEK/ERK pathway is involved in purinergic receptor, such as P2X 7 R, mediated excitotoxic neuronal injury, and neuroprotection [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The local synergy of radiotherapy and CpG was independently verified by a second group in a glioma model 97 . Although the exact mechanism of CpG-mediated radiosensitization is not known, studies have suggested that CpG increases both mTOR activation and autophagy 102 , decreases expression of Oct-4- mediated renewal 103 , and increases NF-kB signaling and nitric oxide production 94 .…”
Section: Introductionmentioning
confidence: 99%
“…When the stress is mild, autophagy can degrade and recycle damaged or unwanted cellular constituents in autophagolysosomal vesicles to provide additional energy supply during stress, which has an essential effect in quality control of organelles and cellular adaptation to stress (13). However, several reports demonstrate that various drugs in combination with radiation promote autophagic cell death rather than apoptosis significantly contributing to the antitumor effects of radiosensitizing treatment or radiotherapy in glioma (14). Hence, autophagy induced by radiation also functions as a pro-death mechanism.…”
mentioning
confidence: 99%